2005
DOI: 10.1348/014466604x18073
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and peer groups: Results from a longitudinal qualitative study of young people in Northern Ireland

Abstract: Previous research has indicated that young people are under considerable social pressure to take up smoking. This study has therefore sought to explore and better understand the mechanisms through which peer-related social factors operate to encourage young people to smoke. Individual qualitative interviews were held with adolescent children aged 11-12 years (N = 102) within youth clubs based in economically deprived areas of Northern Ireland, and then followed up on two occasions during the subsequent 3 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 44 publications
1
48
0
2
Order By: Relevance
“…These items ('So that others won't kid me' and 'Because my friends pressure me to') relate to direct or overt peer pressure (compliance rather than conformity), whereas the three remaining items relate to indirect or normative peer influence or socialization. The relevance of overt peer pressure has been scrutinized for some years (Denscombe, 2001) and studies have found no effects on substance use in adolescence (Reed & Rountree, 1997;Stewart-Knox et al, 2005). Resistance to peer influence in general, and presumably overt peer pressure in particular, increases with age (Steinberg & Monahan, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These items ('So that others won't kid me' and 'Because my friends pressure me to') relate to direct or overt peer pressure (compliance rather than conformity), whereas the three remaining items relate to indirect or normative peer influence or socialization. The relevance of overt peer pressure has been scrutinized for some years (Denscombe, 2001) and studies have found no effects on substance use in adolescence (Reed & Rountree, 1997;Stewart-Knox et al, 2005). Resistance to peer influence in general, and presumably overt peer pressure in particular, increases with age (Steinberg & Monahan, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Focus groups mimic 'natural' peer groups so that the data will likely be authentic, rich and informative. In contrast, one-to-one interviews, although yielding valuable data about individual meanings (Stewart-Knox et al, 2005), can nonetheless invite abstract, de-contextualised themes, which say little about the actual construction and negotiation of smoking in social settings. Focus groups have long been used in social science research, including health psychology (Crossley, 2000;Wilkinson, 2003), and can be particularly useful in identifying both diverse individual accounts and prevailing social factors which influence and constrain actions.…”
Section: Methodsmentioning
confidence: 99%
“…friendly ' (p. 1865). The notion of systematic pressure and coercion to smoke cigarettes is becoming increasingly rejected by smokers and smoking researchers, and Stewart-Knox et al (2005) have argued there is little objective evidence of 'pressure' being applied in most cases of smoking initiation.…”
Section: The Role Of Peers and Friendsmentioning
confidence: 99%